2002
DOI: 10.1046/j.1464-410x.2002.02834.x
|View full text |Cite
|
Sign up to set email alerts
|

Gap junctions and connexin expression in human suburothelial interstitial cells

Abstract: Objective  To determine whether suburothelial interstitial cells of the human bladder express gap junctions, and if so, to establish their extent and composition, using immunocytochemistry, confocal microscopy and electron microscopy. Materials and methods  Bladder tissue was obtained at cystectomy; the tissue was: (i) frozen for cryosectioning and Northern blot analysis; (ii) fixed and embedded for standard thin‐section electron microscopy; and (iii) processed using low‐denaturation conditions in Lowicryl for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
212
4
6

Year Published

2006
2006
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 228 publications
(231 citation statements)
references
References 27 publications
9
212
4
6
Order By: Relevance
“…Furthermore, the apparently smooth and regular contractions and lack of obvious twitching movements suggest that the mutant SMCs are organized and do communicate with each other to propagate a coordinated contraction. Consistent with this, expression and localization of connexin 45, a component of ureteric smooth muscle gap junctions (21,22), were comparable in wild-type and Dlgh1 Ϫ/Ϫ ureter (Fig. 5 C and D).…”
supporting
confidence: 77%
“…Furthermore, the apparently smooth and regular contractions and lack of obvious twitching movements suggest that the mutant SMCs are organized and do communicate with each other to propagate a coordinated contraction. Consistent with this, expression and localization of connexin 45, a component of ureteric smooth muscle gap junctions (21,22), were comparable in wild-type and Dlgh1 Ϫ/Ϫ ureter (Fig. 5 C and D).…”
supporting
confidence: 77%
“…Alterations to BICC function have also been reported in OAB and obstructed bladder in both humans and animal models (79,92,(94)(95)(96)(97). Increased expression of connexin 43 has been reported in patients with OAB, suggesting increased signal transduction between BICCs and BSM cells, potentially leading to motility problems (98,99). This cell is just beginning to attract attention as a possible contributor to bladder motility disorders but it is not currently known whether alterations in BICCs are primary or secondary to disease processes.…”
Section: Bladder Icc: An Old Cell Newly Implicated In Lower Urinary Tmentioning
confidence: 99%
“…In some of the cells, PDE2 was found co-localized with vimentin, a specific feature of ICs and neurons, thereby confirming earlier findings describing immunolabeling for ICs in cardiac tissue and the urogenital tract (Figure 3c). [13][14][15][16][17] Staining specific for PDE11A (dual-substrate PDE) was observed in single nerve trunks located in the clitoral stroma (Figure 1f). In contrast, no labeling indicating PDE2 or PDE5 was observed in nerve fibers or nerve endings (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…28 It has been suggested that ICs may have a pivotal role as so-called pacemakers and mediators of neurotransmission in the bladder, urethra and penile erectile tissue. [14][15][16][17]29 The role of ICs in the clitoris remains to be established. Some hypotheses have been proposed: adult mesenchymal cells, which might participate in (a) intercellular signaling or (b) chemo-mechanical transducing or act as (c) players in pace-making through direct cell-to-cell communication.…”
Section: Discussionmentioning
confidence: 99%